2019
DOI: 10.1016/j.ekir.2019.05.802
|View full text |Cite
|
Sign up to set email alerts
|

Mon-016 a Retrospective Study on Clinicopathological Diagnosis of Nephrotic Syndrome – A Single Centre Experience in Sri Lanka

Abstract: statistical difference between groups (p=0.05). The mean of UMAC was 1258.92AE765.19 pg/ml, with significant differences between the groups; although, no differences were found in the UMAC levels with to the degree of fibrosis (p= 0.10), subjects without fibrosis had the lowest levels of UMAC (770.1AE579 vs 1680.31AE490.1 severe fibrosis). The 100% of patients received induction treatment with corticosteroids, 88% ACEI, 84% statins, 16% steriods+CNi, 8% calcium channel blockers. The basal UMAC levels were lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Our findings were similar to the reports from other South Asian countries, America, Egypt, Spain and Iran, where the most common diagnosis was FSGS [ 13 , 15 22 , 35 – 38 ], Other studies from Europe, East Asia and Australia showed conflicting findings where they reported IgAN to be the most prevalent histopathological diagnosis [ 6 12 , 14 , 39 45 ]. Nevertheless, some studies in South Asia had different results as well, where they reported MCD [ 46 , 47 ] and DPGN [ 29 ] as the most frequent diagnosis. Studies done in Thailand [ 48 ], Oman [ 49 ], Saudi Arabia [ 50 ], South Africa [ 51 ] and Serbia [ 30 ] showed lupus as the most common diagnosis (Table 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were similar to the reports from other South Asian countries, America, Egypt, Spain and Iran, where the most common diagnosis was FSGS [ 13 , 15 22 , 35 – 38 ], Other studies from Europe, East Asia and Australia showed conflicting findings where they reported IgAN to be the most prevalent histopathological diagnosis [ 6 12 , 14 , 39 45 ]. Nevertheless, some studies in South Asia had different results as well, where they reported MCD [ 46 , 47 ] and DPGN [ 29 ] as the most frequent diagnosis. Studies done in Thailand [ 48 ], Oman [ 49 ], Saudi Arabia [ 50 ], South Africa [ 51 ] and Serbia [ 30 ] showed lupus as the most common diagnosis (Table 6 ).…”
Section: Discussionmentioning
confidence: 99%